2012
DOI: 10.1345/aph.1r022
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Medication Information for the Primary Care Physician and the Geriatric Patient at Discharge

Abstract: Discrepancies between the patient discharge medication list and the medication information in the discharge letter for the primary care physician occur frequently. This may be an important source of medication errors, as confusion and uncertainty about the correct discharge medications can originate from these discrepancies. Increasing numbers of drugs involve a higher risk for discrepancies. Medication reconciliation between both lists is warranted to avoid medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
4
26
1
2
Order By: Relevance
“…The controlled pre-post design on physically separated departments was evaluated as the best possible design for this pilot evaluation [19,20]. The geriatric department was chosen because of previously conducted research and the infectious disease department was chosen for practical reasons and convenience because it was located next to the geriatric department [14,21,22]. A 29-bed cardiology department and 29-bed neurology department were selected as control departments.…”
Section: Design and Settingmentioning
confidence: 99%
“…The controlled pre-post design on physically separated departments was evaluated as the best possible design for this pilot evaluation [19,20]. The geriatric department was chosen because of previously conducted research and the infectious disease department was chosen for practical reasons and convenience because it was located next to the geriatric department [14,21,22]. A 29-bed cardiology department and 29-bed neurology department were selected as control departments.…”
Section: Design and Settingmentioning
confidence: 99%
“…During periods of transition between healthcare settings (especially at hospital discharge), patient safety can be compromised by medication errors resulting from incomplete information and lack of coordination with the receiving care provider [1][2][3]. Medication reconciliation (MedRec) has been a priority in several national patient safety campaigns [4][5][6] and healthcare policies.…”
Section: Introductionmentioning
confidence: 99%
“…A clinician generally spends at least one-third of this documentation time, that is, approximately 1 hour per day, writing and correcting DS [5]. Despite this effort, DS often have considerable shortcomings regarding their completeness and quality [6,7], which is especially true for the prescription of medications [8]. Studies have consistently shown that, at most, only 70% of the DS meet the requirements established in the guidelines, and up to 40% are incorrect in some way [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%